CORRELATIONS BETWEEN FERRITIN LEVELS AND CREATININE IN PEDIATRIC THALASSEMIA PATIENTS PRODIA CILEGON - Diah Prihatiningsih Prihatiningsih; Ulfianjani; Ni Komang Ayu Resiyanthi (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Thalassemia is a blood disorder that is passed down genetically from parents to their children. The body cannot form normal red blood cells resulting in them being damaged easily and having a short life of less than 120 days and anemia, requiring continuous blood transfusions to maintain hemoglobin levels in the body. A history of repeated blood transfusions can cause excess iron in the body which is characterized by an increase in serum ferritin levels which can cause damage to kidney function by looking at creatinine levels. The purpose of this study was to determine whether there is a relationship between ferritin and creatinine levels in children with thalassemia. This study used a quantitative method with a cross sectional approach. The sampling technique used in this study was the total sampling technique. The sample used was 12 samples. Data processing in this study used the Shapiro-Wilk Normality test and the Pearson Correlation test in bivariate analysis. The results of the analysis of this study indicate that there is no significant relationship between the ferritin and creatinine levels in children with thalassemia where the value of Sig. 0.212 > 0.05 (p> 0.05), and shows a significant negative correlation of -0.389. This study in thalassemia children had high ferrtin levels but creatinine levels were still within normal limits.